Peran Cyberloafing Terhadap Produktivitas Karyawan Dengan Kesehatan Mental Sebagai Pemediasi - Triyanti, Triyanti; Amelia, Windharti; Maharani, Anita; Pandu, Thenry Linda Sharron (Jurnal Manajemen, 2022)
This study aims to determine the effect of Cyberloafing and Productivity with Mental Health as a mediator. This research uses a quantitative approach method and the sample is taken using a random probability sampling technique with the population being employees of companies in Indonesia that carry out cyberloafing. Data collection was done online using google form and resulted in 193 responses that could be used. The results showed that all hypotheses were not supported, which means that cyberloafing had no effect on mental health and productivity. Further testing with Multi-Group Analysis (MGA) found that the characteristics of the respondents showed different results. In male respondents, cyberloafing had a positive effect on productivity. The respondents from service industry employee group also showed similar results, cyberloafing had a positive effect on productivity. Meanwhile, in respondents with married status showed that cyberloafing had a negative effect on mental health and productivity. These interesting findings from the test results on different characteristics of respondents can enrich studies on cyberloafing, mental health and employee productivity. The results obtained from this study are expected to provide benefits for company management in regulating internet use policies during working hours to ensure employee productivity is maintained.